Теоретическая оценка механизма классификации тонких магнитовосприимчивых материалов - Надутый, В. П.; Челышкина, В. В.; Сухарев, В. В. (НТУ "ХПИ", 2014)
Изложены результаты исследований процесса гидроклассификации с использованием постоянных магнитных полей для тонких материалов с магнитовосприимчивой компонентой (железомагнетитовые и титаномагнетитовые руды, ильменитовые пески и др. с крупностью частиц менее 150 мкм). Решены следующие задачи: определена плотность магнетитовых флоккул, скорость осаждения сферических и цилиндрических флоккул в магнитном поле, установлена зависимость скорости осаждения от напряженности магнитного поля, получены уравнения равнопадаемости магнитных (флоккул), немагнитных частиц и сростков. Полученные результаты позволяют определять крупность частиц при классификации для разных скоростей восходящего потока и напряженности магнитного поля для существующих гидроклассификаторов и проектировать новые магнитно-гравитационные аппараты.

The results of studies of hydro-classification process, with use of the constant magnetic fields, for thin magneto-spirillum materials, which are having magneto-spirillum component (iron ores and titanium-magnetite ores, ilmenite sands and others with the particles’ size less than 150 mk) are presented here. The following tasks are solved: density of magnetite floccules is determined; the deposition rate of spherical and cylindrical floccules in a magnetic field is determined; the dependence of the deposition rate from magnetic field strength is determined; the equations of equal fall of magnetic (floccules), non-magnetic particles and clusters are obtained. Acquired results allows to determine the particles’ size in classification for different speeds upstream and magnetic field strength for existing hydro-separators, and to design a new magnetic-gravitational devices.
Theoretical assessment of the mechanism of thin magneto-spirillum materials classification
Keywords: гидроклассификация; магнитное поле; флоккулы; скорость осаждения; hydro-classification; magnetic field; floccules; deposition rate